Sejarah Perkembangan Bahasa Melayu Menjadi Bahasa Indonesia - Samuel Mamonto (Journal on Education, 2023)
The Indonesian language that we currently speak has its roots in one of the regional tongues spoken throughout the archipelago. For four reasons, the Malay language has a chance of dominating the Archipelago: 1) The Sriwijaya people are naturally inclined to trade. 2) Sriwijaya, the epicenter of the Buddhist movement, and 3). In educational institutions, Malay is the medium of instruction. 4) The official language of conferences between regional organizations is Malay. The data cannot have come from field research because the library research method makes this study more current. Ten congresses for the Indonesian language were convened in order to preserve its existence. The first congress took place in Solo from June 25–28, 1938. From October 28 to November 1, 1954, the city of Medan hosted the second conference. Jakarta hosted the Third Congress from October 28 to November 2, 1978. Between November 21 and 26 of 1988, Jakarta hosted the Fourth Congress. Jakarta hosted the V Language Congress from October 28 until November 3, 1988. Jakarta hosted the VI Congress from October 28 to November 2, 1993. On October 26–30, 1998, Jakarta hosted the VII Congress. VIII Congress, 14–17 October 2003, Jakarta Jakarta hosted the IX Congress from October 28 to November 1, 2008, and the X Indonesian Language Congress from October 28 to October 31, 2013.